Integrating technological innovation in the halal industry: An analysis using PRISMA - Riani, Ririn; Ikhwan, Ihsanul; Rusydiana, Aam Slamet (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This study aims to provide a comprehensive evaluation of the integration of digitalization and technological advancements in the halal industry, highlighting their implications for industry development and addressing key challenges and opportunities.Methodology – We used the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) methodology to conduct a systematic literature review, analyzing 54 research papers published between 2014 and 2024.Findings – This study identifies the challenges and opportunities in adopting technologies such as IoT, blockchain, and AI within the halal sector, and offers suggestions for overcoming these challenges based on the existing literature. The study finds that adopting advanced technologies is essential for the sustainable growth of the halal market and emphasizes the importance of creating explicit regulations and fostering cooperation for technological innovation.Implications – This study has significant implications for academic researchers, policymakers, and industry practitioners by providing insights into the intersection of technology and halal industry. Originality – The originality of this study lies in its systematic exploration of the crucial role of technology in halal market growth and sustainability. This encourages industry professionals to adopt advanced technologies to enhance product visibility and regulatory compliance.